The identification and biochemical properties of the catalytic specificity of a serine peptidase secreted by aspergillus fumigatus fresenius - Silva, Ronivaldo Rodrigues da [UNESP]; Caetano, Renato Cesar; Okamoto, Debora Nona; Gonalves de Oliveira, Lilian Caroline; Bertolin, Thiago Carlos; Juliano, Maria Aparecida; Juliano, Luiz; Oliveira, Arthur H. C. de; Rosa, Jose C.; Cabral, Hamilton (Bentham Science Publ Ltd, 2014)
Aspergillus fumigatus is a saprophytic fungus as well as a so-called opportunist pathogen. Its biochemical potential and enzyme production justify intensive studies about biomolecules secreted by this microorganism. We describe the alkaline serine peptidase production, with optimum activity at 50 °C and a pH of 7.5 and a reduction in proteolytic activity in the presence of the Al+3+3 ions. When using intramolecularly quenched fluorogenic substrates, the highest catalytic efficiency was observed with the amino acid leucine on subsite S3 (60,000 mM-1s-1) and preference to non-polar amino acids on subsite S3. In general, however, the peptidase shows non-specificity on other subsites studied. According to the biochemical characteristics, this peptidase may be an important biocatalyst for the hydrolysis of an enormous variety of proteins and can constitute an essential molecule for the saprophytic lifestyle or invasive action of the opportunistic pathogen. The peptidase described herein exhibits an estimated molecular mass of 33 kDa. Mass spectrometry analysis identified the sequence GAPWGLGSISHK displaying similarities to that of serine peptidase from Aspergillus fumigatus. These data may lead to a greater understanding of the advantageous biochemical potential, biotechnological interest, and trends of this fungus in spite of being an opportunist pathogen. © 2014 Bentham Science Publishers.
Keywords: Aspergillus fumigatus; catalytic specificity; intramolecularly quenched fluorogenic substrates; opportunistic pathogen; saprophytic lifestyle; serine peptidase